Limited in vivo conversion of dietary D3 to 25-OH-D3 in rainbow trout and undetectable endogenous photo-production of D3 in indoor-raised fish - Rider, S.; Chenal, E.; Guy, B.; Cabo-Valcarce, P.; Chatelle, C.; Schattner, A.; Modugno, C.; Etheve, S.; Santigosa, E. (Aquaculture, 2025)
Vitamin D is essential for salmonids and is routinely supplemented in feeds as cholecalciferol (D3). As an intermediate metabolite in the in vivo conversion of D3 to active vitamin D (1,25-OH-D3), directly adding calcifediol (25-OH-D3) to feed may improve vitamin D status. An 84-day feeding trial was conducted in rainbow trout (Oncorhynchus mykiss) raised indoors, to compare dietary 25-OH-D3 and D3 at levels of 200, 400, or 800 μg/kg. Zootechnical performance and the profiles of vitamin D metabolites in plasma, muscle, and liver were assessed. D3 and 25-OH-D3 appeared in plasma, muscle, and liver in a dose-dependent manner. Both metabolites supported optimal zootechnical performance and maintained vitamin D status at all inclusion levels, as indicated by body weight, feed conversion, specific growth rate, and plasma 1,25-OH-D3 concentrations. Plasma and muscle 25-OH-D3 profiles showed that the conversion of dietary D3 to 25-OH-D3in vivo was limited. Additionally, undetectable levels of D3 in fish that did not receive this metabolite in their feed indicated the lack of any significant endogenous photo-production of D3. This study demonstrates that 25-OH-D3 can support growth in salmonids. While adding D3 to fish feeds increases respective levels in the body, the conversion of D3 to 25-OH-D3 is limited. Therefore, to raise in vivo levels of 25-OH-D3 above this threshold, it needs to be direclty added to the feed. Since salmonids raised indoors do not produce detectable D3 endogenously, they rely on dietary sources to meet their vitamin D requirements. •The in vivo conversion of dietary D3 to 25-OH-D3 is limited in trout.•Photo-production of endogenous D3 is not detectable in indoor-raised trout.•Dietary 25-OH-D3 can sustain normal growth in trout.•Dietary 25-OH-D3 supplies both the circulation and muscle with 25-OH-D3.